TINJAUAN YURIDIS PERTANGGUNGJAWABAN PIDANA PENCEMAR LINGKUNGAN HIDUP - Bangun Patrianto (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2005)
Conventional Law teaching express that each every deed impinge the law harming other party hence side the maker is obliged to change with a number of money utilize to cure if proven in the face of mistake conference of maker but the rule have been infiltrated by principle of justice absolute responsibility strict liability what cirrithe core important for example incidence direct responsibility and at once at the time of the happening of deed, so that needn’t be related to by mistake element fault, schuld.